Bimodal Porous Scaffolds by Sequential Electrospinning of Poly(glycolic acid) with Sucrose Particles. (30th March 2010) - Wulkersdorfer, B.; Kao, K. K.; Agopian, V. G.; Ahn, A.; Dunn, J. C.; Wu, B. M.; Stelzner, M.
Abstract : Electrospinning is a method to produce fine, biopolymer mesh with a three-dimensional architecture that mimics native extra-cellular matrix. Due to the small fiber diameter created in this process, conventional electrospun scaffolds have pore sizes smaller than the diameter of most cells. These scaffolds have limited application in tissue engineering due to poor cell penetration. We developed a hybrid electrospinning/particulate leaching technique to create scaffolds with increased porosity and improved cellular ingrowth. Poly(glycolic acid) (PGA) and a sucrose-ethanol suspension were electrospun in equal, alternating sequences at intervals of one, two, and ten minutes each. The scaffolds revealed fiber mesh with micropores of 10 μ m and uniformly distributed sucrose particles. Particulate leaching of sucrose from the one- or two-minute scaffolds revealed honeycomb structures with interconnected macropores between 50 and 250 μ m. Sucrose leaching from the ten-minute scaffolds resulted in laminated structures with isolated macropores between 200 and 350 μ m. Macropore size was directly proportional to the duration of the sucrose spinning interval. After 24 hours of cell culture, conventionally spun scaffolds demonstrated no cellular penetration. Conversely, the PGA/sucrose scaffolds demonstrated deep cellular penetration. This hybrid technique represents a novel method of generating electrospun scaffolds with interconnected pores suitable for cellular ingrowth.